The brazilian forestry Project - Reis, Mauro Silva (Pesquisa Agropecuaria Brasileira, 2014)
The basic structure of the Brazilian Forestry Project was set up in the mid 60's with the edition of the Forestry Code (1965), the formulation of the policy of Fiscal Incentives for Reforestation (1966), and the creation of the Brazilian Institute for Forestry Development (IBDF 1967). The regulation of the use of Forestry Resources in the Forestry Code foresees: (1) the definition of permanent preservation areas, given their connection and strategic situation in face of the needs of soil protection and hydrological resources; (2) guidelines for the rational utilization of resources, comprising the obligatory replacement of forests by the big consumers of forest raw material; (3) limitation to the removal of the forest cover in private property areas (80% in the Center-South and 50% in the Amazon); and (4) the main categories of Conservation Units (National Parks and National Forests) to be maintained by the Public Authority. The policy of fiscal stimulus to reforestation activities, although foreseen in the Code, was established from specific legislation in 1966, with later reformulations designed to improve the mechanisms involved with the expansion of reforestation. Consequently, the reforested area from fiscal incentives in the country was in the range of 100 to 250 thousand hectares per year, between 1968 and 1973, and of 300 to 400 thousand hectares, between 1973 and 1982, having reached an approximate total area of 5 million hectares by the end of that year. With the creation of the Brazilian Institute for Forestry Development, one has aimed to endow the Forestry Sector with an institution of wide normative capability and influence at a national level, to stimulate and regulate the forest activities. IBDF was attributed the tasks of the formulation of the Forest Policy, as well as the orientation, coordination and execution of all necessary measures to the rational utilization, protection and conservation of renewable natural resources, and to nation's forestry development. The diverse situations of the Brazilian Forestry question, either as to the availability and quality of forest resources, or as to the distinct regional social-economic stages of the country, imply a gradual adoption of norms and measures directed at a differentiated set of specific problems. The advanced process of land occupation in the Center-South, coupled with the expectation of expansion of the per capita consumption levels of forest products, conditioned the establishment of extensive forest plantations linked, basically, to supplying raw material at reduced costs to strategic segments of the national economy, whose establishment and consolidation one strived to ensure (pulp and paper, charcoal pig-iron industry and processed wood). As a result of the importance quickly assumed by the expansion of the reforestation related to the more dynamic sectors of the national economy, there were significant repercussions on the foreign trade of forest products, on the magnitude and profile of the demand for qualified technical personnel, in addition to a strong conditioning of research orientation. A significant indicator of evolution of the sector during the 70's is the structure of the foreign trade of forest products, with their import and export schedules revealing the level of self-sufficiency, diversification and competitiveness of the domestic industry. The magnitude and profile of this foreign trade experiences a substancial transformation in this period: while in the beginning of the 70's sawnwood and log exports represented more than 70% of the value of exports, in the last years of the decade pulp and paper exports were responsible for more than 50% of the exported value. And, if in the years of 1975 to 1977 the total of forestry exports was around 240 million dollars per year, in 1980 it reached the mark of 1 billion dollars. Finally, the expansion of imports during 1970-1980 was strongly inferior to the growth of exports, for these expanded tenfold, while those only threefold. In the more recent years, the contribution of the forestry sector to the industrial consumption of energy has enlarged, as result of the efforts to reduce our dependence on foreign oil: only the segments of cement, pulp and paper consumed around 7 million cubic meters of roundwood in substitution to fuel oil, which represented savings of foreign exchange of the order of 130 million dollars, with the expectation that these figures shall be duplicated during the next two years. Set against the stage of urbanization, industrialization and the utilization of land in course in the Center-South, the Brazilian Amazon shows reduced demographic indexes, together with the recent establishment of agricultural projects and forest exploitation. The fragility of most of the soil in this region, besides indicating a predominantly forestry vocation, also shows that, as an object of forest inventories in the area, one should strive to quantify the removal of the forest cover, given the preoccupation of the government and of the society with the occurrence of environmental damages. In the sphere of preservation of renewable resources, the governmental action has been looking for an enlargement of the protected areas through the creation and establishment of conservation units such as national parks and biological reserves. Evidence of this orientation is that the expansion of protected areas under these units, along the actual governmental period, has been raised from 2.5 million hectares to 12 million hectares, with great emphasis on the preservation of ecological samples in the Brazilian Amazon. A role of extreme importance to the Development of the Forestry Sector has been played by forestry research. The establishment, at a national level, of the "Forestry Research and Development Project - PRODEPEF" in 1971, between the United Nations Development Program, through FAO, and the Brazilian Government, represents a significant step of the effort of research. Among the research lines established, the following may be mentioned: (1) the adaptation of species of rapid growth aimed at the formation of homogeneous forests; (2) the management of tropical forests; and (3) technology of forest products aiming at the identification of physical and mechanical characteristics of those less known species in domestic and international trade. The increasing importance that the function of research has assumed for the development of the sector has led to the creation of a National Program of Forestry Research in 1978, as result of an agreement between IBDE and EMBRAPA. As a consequence, a Model of Research has been defined, which engages these two institutions, the universities and private companies in the formulation and execution of research projects, indispensable to enlarge and deepen the knowledge on the country's forest resources. The expansion of the scope of Forestry Research has facilitated a more comprehensive approach capable of taking into account, in addition to the more immediate problems such as the utilization of the forests for industrial and energetic purposes, the investigations needed for the generation of informations required for an increasing activity of reforestation in the Brazilian Northeast as well as for those aspects related to soil and water conservation.